U.S. Pharmacist Opinions Regarding the Rescheduling of Hydrocodone Combination Products: A Pilot Study - Jordan R. Covvey; Andrea R. Pfalzgraf; Peter P. Cohron (MDPI AG, 2015)
In October 2014, the Drug Enforcement Administration in the U.S. reclassified hydrocodone combination products (HCPs) from Schedule III to Schedule II, initiating one of the most significant and controversial regulatory changes for opioids in recent national history. The aim of the present study was to determine community pharmacist opinions on the effect of the rescheduling of HCPs on their personal practice. A web-based pilot survey was emailed to a convenience sample through online newsletters of professional pharmacy organizations in Pennsylvania, Kentucky and West Virginia in April/May 2015. A total of 62 surveys were initiated, yielding 56 complete responses. More than 75% of respondents noted increases in their workload as a result of the rescheduling of HCPs. Opinions regarding the intended outcomes of rescheduling were only weakly positive, with only 37.5% of respondents believing it has increased safety and 44.6% of respondents believing it has lessened abuse/diversion. For overall attitudes regarding the rescheduling, respondents were split between positive (26.8%), neutral (26.8%) and negative (46.4%). These initial data suggest that pharmacists have encountered barriers in practice resulting from the rescheduling. Further expanded work is necessary to verify these results from the small sample, and to assess the intended effects of the rescheduling upon the safe and effective use of hydrocodone.